Fundamental Study of Detection Method of Swaying Angle of Container for Linear Motor Driven Container Crane System - Yamamoto, Shigehiro; Taniguchi, Yuki; An, Sangbeak; Azukizawa, Teruo (Marine Engineering, 2010)
The authors had proposed a linear motor driven container crane system which could realize a high speed, compact, and low maintenance crane system. In this system, the linear motor is used to control swaying motion of the spreader with the container in addition to drive trolley chassis. We proposed a novel detection method for the swaying angle of the suspended spreader with the container using an acceleration sensor attached to the linear motor driven trolley chassis.In this paper, the fundamental characteristics of the proposed swaying angle detecting method were investigated. Simulated results and experimental data showed the validity of the proposed swaying angle detection method.